Growth factors for construction companies in Malaysia - Bakar, Abu Hassan Abu; Said, Ilias; Shafiei, Mohd Wira Mohd; Razak, Arman Abd.; Yusof, Mohamad Nizam (2008)
In General, most firms have multiple objectives to sustain and success in their business. For the short term, firms pay more attention to profit maximization. However for the long term, profit is no longer a prime objective because one of the objectives which may dominate the management of firm is growth. It is a change in assets, turnover, profits, number of employees and share price during the process of organizational change. Growth does not take place automatically, but must be planned strategically and implemented effectively by the organizations. The strategies for growth are vital for companies’ success. Thus, the main objective of this paper is to establish factors determining growth of construction companies in Malaysia. This paper starts of with reviewing past literature on growth of firm and attempt to establish a new area that need further investigation. Study focuses on the growth factors that responsible for the growth of construction companies in Malaysia.